A review of measures used in the screening, assessment and diagnosis of dementia in people with an intellectual disability. Issue 5 (9th February 2018) - McKenzie, Karen; Metcalfe, Dale; Murray, George
Abstract : Background: The increasing number of individuals with an intellectual disability who are at risk of developing dementia highlights the need to use measures with strong psychometric properties as part of the screening, assessment and diagnostic process. Method: Searches were made of clinical and good practice guidelines and English language journal articles sourced from Proquest, Web of Science and Scopus databases (up to July 2017) for tools which were designed or adapted for the purpose of helping to diagnose dementia in people with intellectual disability. Results: Based on a detailed review of 81 articles and guidelines, the present authors identified 22 relevant tools (12 cognitive, 10 behaviour). These were reviewed in terms of their psychometric properties. Conclusions: A number of tools were found to be available for use with people with intellectual disability; however, few were specifically standardized for this purpose which also had comprehensive information about reliability and validity.